Isolation, Characterization, and Antitumor Activity of a Novel Heteroglycan from Cultured Mycelia of Cordyceps sinensis - Mei, Yu-xia; Yang, Wei; Zhu, Pei-xin; Peng, Nan; Zhu, Hai; Liang, Yun-xiang (Planta Medica, 2014)
A novel heteroglycan, Cordyceps sinensis polysaccharide 1 (molecular weight 1 17 × 105 Da), was isolated and purified from mycelia of the fungus C. sinensis obtained by solid-state culture. Structural characterization by chemical analysis, GC-MS, FTIR, and NMR spectroscopy showed that C. sinensis polysaccharide 1 was mainly composed of (1 → 6)-linked α-D-Glc and α-D-Gal, with minor β-(1 → 4)-D-Xyl and β-(1 → 4)-D-Man residues probably located in the side chains with a trace amount of α-(1 → 3)-L-Rha residue. In biological assays, C. sinensis polysaccharide 1 significantly inhibited proliferation of sarcoma 180 cells and induced apoptosis in a dose-dependent manner. Further studies will elucidate the antitumor mechanism of C. sinensis polysaccharide 1 and promote its utilization for the development of novel, effective anticancer drugs.
Keywords: Cordyceps sinensis; Clavicipitaceae; heteroglycan; characterization; antitumor activity; apoptosis; Cordyceps unilateralis subclade